PERSEPSI MAHASISWA PERPUSTAKAAN DAN SAINS INFORMASI UNIVERSITAS PENDIDIKAN INDONESIA ANGKATAN 2019 TERHADAP IMPLEMENTASI KODE ETIK PUSTAKAWAN - Dheani Nurfitria (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2021)
Starting in 1988, the Indonesian government has authorized the librarian profession to become a functional position. Functional positions are regulated gradually, and finally with the decision of KEMENPAN RB 132/KEP/M.PAN/12/2002 concerning Functional Librarians. As a profession that the state has recognized, librarians must be responsible for all actions both of fellow librarian professions, organizations, and to themselves. Each member of the Indonesian Librarian Association is responsible for implementing the code of ethics in the highest standards for the needs of users, professions, libraries, professional organizations, and the community. Librarians must not only know about the librarian’s code of ethics, but librarians must also implement it. The purpose of this study is to determine the perception of students class of the 2019 library and information science study program on the importance of implementing the librarian code of ethics. Later, it can provide knowledge to libraries, especially in Indonesia about the importance of implementing a librarian code of ethics. The method used in this study is descriptive with a quantitative approach. The results showed that students of library and information science study program class of 2019 Indonesian Educational University strongly agreed to implement the librarian code of ethics according to IPI with results above 85%. The implementation of the code of ethics will impact the library and the librarian for the achievement of the shared goals of the library.